Evaluation of Tax Obligations for MSMEs in Calculating Personal Income Tax at the South Makassar Pratama Service Office - Nasria (JEKAMI Journal of Accounting, 2023)
This study, conducted by Nasria from the University of Muhammadiyah Makassar, focuses on evaluating tax obligations for Micro, Small, and Medium Enterprises (MSMEs) in calculating Personal Income Tax at the South Makassar Pratama Service Office. The research employs a descriptive qualitative approach, utilizing primary data from agency sources and secondary data regarding the number of MSME taxpayers in South Makassar from 2016 to 2020. The findings indicate that MSME taxpayer compliance in fulfilling tax obligations at the South Makassar Pratama Service Office is generally satisfactory, reflecting increased awareness post the implementation of Government Regulation No. 23 of 2018. However, some MSME taxpayers still face challenges, particularly in understanding financial bookkeeping and effectively managing their tax obligations. The study explores the benefits perceived by MSME taxpayers in calculating Personal Income Tax, emphasizing the positive impact of Government Regulation No. 23 of 2018 on simplifying tax calculations and reducing tax rates. Despite improvements, certain MSMEs encounter difficulties due to inadequate understanding of bookkeeping principles and limited resources for accounting. An analysis of MSME taxpayer compliance levels from 2016 to 2020 reveals a consistent increase in the number of taxpayers, attributing this growth to the facilitative measures introduced by Government Regulation No. 23 of 2018. The study concludes that while MSMEs generally comply with tax obligations, there are still challenges that need to be addressed. Recommendations include encouraging MSMEs to leverage government policies for regular tax payments, organizing outreach activities to enhance understanding, and suggesting further in-depth research in collaboration with MSMEs.